Complete slaking collapse of dike sandstones by fresh water and prevention of the collapse by salt water. (July 2020) - Fujii, Yoshiaki; Saito, Shiori; Oshima, Teppei; Kodama, Jun-ichi; Fukuda, Daisuke; Sakata, Shokichi; Uchida, Kagemi; Matsumoto, Hiroyuki; Dassanayake, Anjula B.N.
Abstract: Slaking is a well-known process, in which the surface of rock masses consisting of rocks such as mudstone, shale, etc. show rapid and complete disintegration when they are subjected to drying and then wetting with fresh water. On the other hand, dried sandstones even if they contain clay minerals such as smectite, etc., usually do not exhibit complete disintegration when they are soaked in fresh water. Instead, they usually show a strength decrease. Their slaking durability is tested by rotating them in a drum which is partially immersed in fresh water and eventually measuring the decrease in weight. On the other hand, it was found that some of the Paleogene sandstones from Kushiro Coal Mine in Japan, were completely disintegrated when they were immersed in fresh water followed by drying, but they were not collapsed when saline water was used instead of the fresh water. It was also shown that sandstones containing calcite did not show the complete breakdown even in fresh water. To understand the complete collapse of sandstones in fresh water and prevention of the collapse by salt water, sandstones sampled from Neogene dikes and Cretaceous at the mine were immersed in pure and salt water with Shikotsu welded tuff for comparison. Only dike sandstones showed a complete collapse in pure water and 3% salt water. Dike sandstone further showed severe time-dependent damage in salt water whose salinity was less than 7%. The results were explained by the dissolution of halite, swelling pressure of montmorillonite, osmotic pressure, etc.